Price Policies in Central Java, Indonesia: Impact on Demand for Urea Fertiliser in Paddy Production and the Resulting Nitrate Contamination - Yahman Yosohardjono, Mulyadi (2000)
Since late 1970's, the Indonesian government has implemented a price support policy on paddy and a price subsidy policy on fertiliser for paddy production. These policies had been successful both in increasing fertiliser use as well as paddy production. Increase in fertiliser use, in particular nitrogen fertiliser, however, also means increase in nitrate contamination in ground water. Nitrate contamination in ground water exceeding 10 N03 mgIL is known to cause ''blue baby" syndrome or methemoglobinaemia and stomach cancer (Lebby and Bogges, 1990). As most of rural population in Java depends on ground water as a source of drinking water, nitrate contamination poses serious threat to society and should be mitigated immediately. This study attempts to evaluate the impact of price support policy on paddy and subsidy policy on fertiliser price on fertiliser use, paddy production, farmers' welfare and nitrate contamination in ground water in Central Java Province Indonesia. Cross sectional data of paddy farms and dug-wells were used in this study. Eight regencies were selected using stratified random sampling based on urea application rates. For each regency, two districts were selected and for each district, five units of farm and five dug-well samples were chosen based on simple random sampling. A translog profit function and cost share function for urea with nitrate contamination were estimated simultaneously for derived demand for urea fertiliser and supply of paddy functions. These functions were then used to evaluate the impact of price policies. Fertilisation of nitrogen in paddy cultivation is the main source of nitrate contamination in ground water. About 86.9 percent of the dug-wells water samples had nitrate contamination with an average of 2.01 ppm N03-N, 1.3 percent had contamination exceeding the maximum admissible requirement for drinking water at 10 ppm. The price subsidy on urea fertiliser and price support on paddy were effective in boosting profit of paddy farms as well as paddy production. The price policies contributed significantly to urea fertilisation rate, and thereby to paddy productivity. At the same time these policies also generated nitrate contamination in rural ground water. Nitrate contamination had not significantly influenced profit as well as demand for urea fertiliser and supply of paddy. Simulation results confirmed that price policies, which did incorporate environmental policy, in particular nitrate contamination, would generate nitrate contamination in ground water. It is likely to continue to increase in the future if environmental consideration continued to be ignored. Hence, the environmental policy should be integrated in price policies.